Governance and Anti-corrupton Diagnostics : Guidance and Tools for Implementation, Monitoring, and Assessment in the Field - Recanatini, Francesca; Morgan, Grace; Laghdaf Cheikh Malainine, Mohamed (World Bank, Washington, DC, 2013)
This guide focuses on one of the more granular approaches to governance improvement, the governance and anti-corruption diagnostic. Governance and anti-corruption diagnostics are used as an initial strategy to identify the nature of governance problems, to target the key sources or institutions associated with these problems, and to establish a baseline and indicators which can be used to make reforms and to measure progress over time. Increasingly, these diagnostics are becoming sectoral in nature, meaning they are customized to assess governance and anti-corruption in a targeted sector. If conducted properly, the diagnostic process informs and catalyzes stakeholders to demand reform. If repeated periodically, these diagnostics can become useful tools to monitor governance and anti-corruption over time. More specifically, governance and anti-corruption diagnostics: 1) Unbundle corruption by type - administrative, capture of the state, bidding, theft of goods and public resources, purchase of licenses and regulations; 2) Identify both weak institutions (which are in need of reform) and strong institutions (which provide examples of good governance); 3) Assess the cost of each type of corruption on different groups of stakeholders; 4) Provide insight into the relationship between corruption, service quality and access, and trust in public institutions; 5) Identify key determinants of good governance; and 6) Serve as a strong foundation for policy recommendations and reform.